The Veil and The Issue of Radicalism: A Study of The Phenomenon of Veil Wearing in Islamic Higher Education - Abdul Wadud Nafis; Zahratul Maujudatul Mufidah; As'ari (Pusat Penelitian dan Penerbitan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Raden Fatah Palembang, 2026)
This study aims to analyze the phenomenon of wearing the veil (Niqab) and its relationship to the issue of radicalism at UIN Kiai Haji Achmad Siddiq (KHAS) Jember. The study used a qualitative approach with a phenomenological method, while data collection was conducted through in-depth interviews, observation, and documentation. Data analysis went through the stages of data reduction, data presentation, and drawing conclusions, while data validity was tested through triangulation of sources and techniques. The results showed that Niqab wearing was influenced by factors of self-identity, hijrah symbols, religious clothing trends, social media, and the desire to protect oneself from a religious perspective. Wearing the veil also creates barriers to nonverbal communication and negative stereotypes that associate it with radicalism. The issue of radicalism was influenced by a weak understanding of religious moderation, exposure to extreme ideologies through digital media, the social environment, and psychological and economic factors of students. Countermeasures were carried out through strengthening religious moderation, positive student activities, early detection, cooperation with authorities, and inclusive dialogue. Thus, the phenomenon of wearing the veil shows that religious symbols cannot be directly linked to radicalism.